Some Remarks on the Nineteenth Century Studies of the Euthyphro in Poland - Mróz, Tomasz (Peitho. Examina Antiqua, 2011)
The present paper examined how Polish philosophers, historians and classicists understood and interpreted Plato’s Euthyphro in the 19th century. The article provides evidence for a twofold interest that Polish readers had for the dialogue in this period. Firstly, Catholic thinkers focused on the ethical issues of the dialogue and supported the revival of the Scholasticism, confirming, at the same time, the vitality of Plato’s thought. Secondly, the text of Plato’s opusculum was a convenient didactic material for various teachers of the Greek language: while the Euthyphro gave them the opportunity to raise ethical and logical issues, they also taught philosophy on the basis of this dialogue.